Leadership : theory and practice - Northouse, Peter Guy (SAGE Publishing, 2022)
"Now with a new chapter on Inclusive Leadership Adopted in thousands of courses in 89 countries and translated into 15 different languages, this market-leading text successfully combines an academically robust account of the major theories and models of leadership with an accessible style and focus on how leadership theory can inform leadership practice. Peter G. Northouse uses a consistent structure for each chapter, allowing readers to easily compare and contrast different theories. Case studies and questionnaires provide students with practical examples and opportunities to deepen their understanding of their own leadership style. Key Features: A consistent chapter structure outlines each approach, how it works, and the major studies behind it, followed by an analysis of the strengths and criticisms for each approach Three case studies in each chapter help students to apply leadership theories in real-world scenarios. Questionnaires within each chapter provides self-assessment and reflection opportunities for each theory presented. New to This Edition: New Chapter on Inclusive Leadership provides a model of inclusive leadership that examines antecedent conditions, leader behaviors, and positive organizational outcomes associated with inclusive leadership 18 new real-world case studies profile leaders around the globe including cases on New Zealand Prime Minister Jacinda Ardern, a mental health program in Zimbabwe, and how a university in the US responds to crisis. New discussion of leadership and morality explores leadership as a neutral process and leadership as a moral process"--